A study on linguistic features Of english civil aviation documents issued by icao - Nguyễn Thị Mai Nga (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This thesis studied linguistic features of English Civil Aviation Documents issued by ICAO (IECADs). An analysis was made to find out linguistic features used in IECADS. Its corpus consisted of 800 sentences withdrawn from three IECADs related to air traffic control. Together with the analysis, a discussion and comments on the lexical and syntactic features and cohesive devices have been made. The process of the study takes readers from the theory of lexicon, syntax and cohesive devices to the conclusion and implication at the end of the thesis. Firstly, data were described in detail in terms of lexical, syntactic features and cohesive devices. Then, the analytic method was used to clarify and categorize data. Besides, the occurrence frequency was applied to withdraw the conclusion on the findings of the research. By these ways, lexical feature were studied according to groups such as words denoting aircrafts, words relating to transportation, approach, separation, rules of the air, airspace, height and flight operation during flight from start-up to landing and meteorology. The syntactic features were illuminated through four types of sentences: simple sentences, complex sentences, compound sentences and compound-complex sentences. And at last, the cohesive devices relying on the references and conjunctions were taken into consideration. From the study of these features, the thesis provided some suggestions effectively that teachers of English can teach English to civil aviation personnnels.